DESIGN PARAMETERS OF BUFFER STOPS - Petr Guziur (Acta Polytechnica CTU Proceedings, 2016)
Paper discuses reasons of building buffer stops and situations that may occur in railway station leading to build safety tracks. Also discusses parameters of buffer stops that enter its design, such as collision speed and kinetic energy absorbing capacity. Furthermore, presents categories of buffer stops depending on principles of absorbing the kinetic energy and points pros and cons of each structure.